The Impact of Capital Structure on the Performance of the Company - Stoiljković, Aleksandra; Tomić, Slavica (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
Determining the optimal capital structure is one of the most complex, but also the most important decisions for any company, given that this decision greatly affects the financial performance, competitiveness and survival of the company. There are a number of theories that explain capital structure and its impact on firm performance, from the initial Modigliani-Miller theory of capital structure irrelevance to firm value, to a number of alternative theories that predict different capital structure impacts on firm value / performance. The paper will present the results of previous empirical research, conducted in different countries, on the impact of capital structure on company performance. The most significant results of the conducted literature analysis generally indicate a positive relationship between capital structure and company performance, and that companies can contribute to the improvement of their performance by using debt, through a higher share of debt in the capital structure. However, some research suggests that when the share of debt in the capital structure becomes relatively high, a further increase in debt may have a negative impact on corporate performance.